(3JbfjGJ GdeMGSHI GdYGeI hab GdfXGe GdeMGSHj GdeGdj GdLOjO (Bscf :s (3GdLGfH GdJWHjbj (B/s - (3WQWGQ, CMeOs; (3efUQ, YHO GdYGdjs ((3GdLRGFQ(B: s (3LShQ(B, s, 2018)
(3YQaJ GdeDSSGJ GdGbJUGOjI GdLRGFQjI eY eWdY GdYGe (B2010 (3GdONhd aj eQMdI MGSeI ef GdEUdGM GdGbJUGOj YeheG, MjK ONd GdfXGe GdeMGSHj GdeGdj GdLOjO ddeDSSGJ GdGbJUGOjI MjR GdJWHjb, hjYJHQ gPG GdCNjQ eSJhMi ef GdeYGjjQ GdeMGSHjI GdOhdjI heYGjjQ GdEHdGZ GdeGdj hbO cGf gPG GdJMhd Vef EWGQ SjGSI GdJbGQH GdJj JfJgLgG GdLRGFQ deSGjQI GdeJZjQGJ GdOhdjI hehGcHI GdJWhQGJ GdGbJUGOjI hGdGLJeGYjI hGdbGfhfjI hGdeYdheGJjI hdbO CMOK JWHjb GdfXGe GdeMGSHj GdLOjO eLehYI ef GdJZjQGJ jJfGhdgG gPG GdcJGH HGdTQM hGdJaUjd aj bSejf(B: (3fXQj hJWHjbj hgh EWdGdI Ydi eLQjGJ GdCMOGK GdJj JJhGJQ cd jhe, hYdi GeJOGO GdSfI, aj cd cjGf eUZQ ef cjGfGJ GdeLJeY GdGbJUGOj hGdeGdj (B((3GdeDSSI(B) (3GdeKbd Hgehe GdJLGQI hGdUfGYI hGdeGd, hGdeJje HGdHMK Yf GdahGFV hGdCQHGM haj SYj ODhH dG jcqd Cgdg hdG jedhf(B. s
(3eQGLY U(B.249s
Keywords: (3GdeMGSHIs; (3GdfXGe GdeMGSHj GdeGdj (B- SCF s